1993
DOI: 10.1088/0022-3727/26/4/010
|View full text |Cite
|
Sign up to set email alerts
|

Emission spectroscopy of the plasma in the cathode region of N2-H2abnormal glow discharges for steel surface nitriding

Abstract: Plasma analysis using emission spectroscopy has been carried out in the cathode fall and the negative glow of N2-H2 abnormal glow discharges for steel surface nitriding. The spatial distributions of the selected excited states of N2, N, N2+, N+, NH, H2, H and Fe have been measured in terms of their dependence on the main process parameters, such as the cathode temperature (400-550 degrees C), H2 percentage in the gas mixture (10-70%) and total pressure in the nitriding reactor (400 and 800 Pa), corresponding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…With regard to the intensive investigation of the glow discharge, experimentally, many techniques such as optical emission spectroscopy, electronic probes and mass spectroscopy have been used to study the behaviours and reaction processes of plasma particles [1][2][3][4][5]. Meanwhile, the advent of fast and accessible computers has led to the development of a large number of physical models to simulate the dc glow discharge, such as the kinetic model [6][7][8], the fluid model [9,10] and the Monte Carlo (MC) model [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…With regard to the intensive investigation of the glow discharge, experimentally, many techniques such as optical emission spectroscopy, electronic probes and mass spectroscopy have been used to study the behaviours and reaction processes of plasma particles [1][2][3][4][5]. Meanwhile, the advent of fast and accessible computers has led to the development of a large number of physical models to simulate the dc glow discharge, such as the kinetic model [6][7][8], the fluid model [9,10] and the Monte Carlo (MC) model [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the figures for the system with a GaAs cathode, one can note the following: (i) the discharge current in H 2 has a stable form; however, unstable V -I forms are observed in air (see oscillations for curves under L 1 and L 2 ); (ii) although higher voltages are applied to the system, discharge currents for H 2 are lower than those for air; (iii) the current in air is increased more than that for H 2 when the illumination intensity L is increased. Rusnak and Vicek [64] studied the effect of different percentages of N 2 -H 2 gas mixture on the electrical characteristics of the discharge such as the V -I characteristic curves, U B , the cathode fall thickness, the axial distribution of potential and electric field. They found that the addition of a small amount of hydrogen leads to a significant increase in the discharge current.…”
Section: Resultsmentioning
confidence: 99%
“…In the experimental study, the dissociation rate of N 2 [3] and the amount ratios of various nitrogen species [5] are examined through measuring the intensities of the characteristic spectral lines and their ratios. In Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most inexpensive, easy-to-use and nonperturbative techniques to characterize the plasma is optical emission spectroscopy (OES). Due to these advantages, OES is employed to monitor the deposition process [4] , the steel surface nitriding [5] and the dissociation of nitrogen [3] in glow discharges in both institutions and industry. Usually the light emitted by radiative transitions among excited states in the plasma is collected by an optical fibre, and analysed with a spectrometer based on charge coupled device (CCD), resulting in an optical emission spectrum.…”
Section: Introductionmentioning
confidence: 99%